A Practical Guide to Family Therapy - Wallis, Andrew; James, Kerrie; Rhodes, Paul (Taylor & Francis, 2024)
Grounded in systemic family therapy and drawing on a variety of other models to enhance skills development, this book is a comprehensive, practical guide to working with families. This second edition is thoroughly updated and includes new chapters which cover working with First Nations Families, diversity and family therapy, understanding emotions, and dialogical reflective processes. The book begins with a focus on the therapeutic relationship and use of self as a foundation, and from there provides the reader with practical, skill-oriented guidelines for working with families. From the first session to addressing the complexities of separated parents, parent-child relational breaches, family of origin issues, wider systems, managing emotions, diversity, and much more, the book takes the reader through core practices that will become essential skills for family work. Written by an expert team of authors committed to innovative and contextual practice, this book is for experienced clinicians who want to learn to work with families and for beginning therapists to learn from a structured approach to developing complex skills.